What's Going On: "Partisan" Worries, and Desires to Discuss Trump-Era Events in School. Issue 10 (October 2021) - Pollock, Mica; Yoshisato, Mariko
Background/Context: This article explores how the classic U.S. educator effort to stay politically "nonpartisan" when teaching became particularly complicated in an era of spiking K–12 harassment, when government officials openly targeted and denigrated populations on the basis of race, national origin, gender, sexuality, and religion. We share research on a pilot (2017–2019) of #USvsHate, an "anti-hate" initiative we designed and studied with K–12 educators and students in the politically mixed region of San Diego, California. Purpose/Objective/Research Question/Focus of Study: #USvsHate sought to respond to a national spike in bigotry, harassment, and hate crimes by inviting "anti-hate" learning and messaging in an explicitly nonpartisan manner. Analyzing educator interviews and student focus groups from the project pilot, we explore a core tension raised throughout #USvsHate participation: Some participating educators feared that such work to include "all" as equally valuable would seem partisan to critics and so be deemed off-limits. We focus on this tension in part to support educators continuing to grapple with it in a deeply divided country. Population/Participants/Subjects: Pilot participants came from 12 diverse districts in our region, including 53 teachers and 427 students who submitted anti-hate messages to contests, with more than 3, 300 students participating overall. We interviewed piloting K–12 teachers (18) and students (30) from traditional public schools and public charter schools. Research Design: Unlike more structured interventions, #USvsHate's core shared experience is its open-ended invitation to "anti-hate" teaching and messaging. As ethnographically trained researchers, we spent spring 2018 and the 2018–2019 school year studying experiences of #USvsHate's lessons and messaging efforts, feeding input continually back into project design in a participatory process. Teachers and students joined interviews and focus groups voluntarily. We also talked with dozens more teachers in design sessions and recruitment gatherings. Data Collection and Analysis: We used discourse analysis techniques piloted in studies on race talk to identify trends in participants' responses and across individuals, coding for a key phrase found in focus group data: Across schools, students stated that #USvsHate offered a necessary chance to discuss "what's going on." Conclusions/Recommendations: Students interviewed considered it obviously educators' professional responsibility to address current incidents of denigration, harassment, bigotry, and threats targeting groups in schools, communities, and society—all of which they termed simply "what's going on." Educators agreed but that feared "anti-hate" work now might be deemed partisan and so off-limits to educators. We explore the deep complexity of this worry—and we explore educators' and students' attempting to discuss current events of harm as simply part of educators' jobs.